Focusing on the role of secretin/adhesion (Class B) G protein-coupled receptors in placental development and preeclampsia - Yin, Aiqi; Guan, Xiaonian; Zhang, Jian V.; Niu, Jianmin (Frontiers in Cell and Developmental Biology, 2022)
Preeclampsia, a clinical syndrome mainly characterized by hypertension and proteinuria, has a worldwide incidence of 3-8%, causes high maternal mortality and is a risk factor highly associated with maternal and offspring cardiovascular disease. However, the etiology and pathogenesis of preeclampsia are complex and have not been fully elucidated. Obesity, immunological diseases and endocrine metabolic diseases are high-risk factors for the development of preeclampsia. Effective methods to treat preeclampsia are lacking, and delivery remains the only treatment for preeclampsia. There are numerous pathogeneses of preeclampsia, including poor placentation, uteroplacental malperfusion, oxidative stress, endoplasmic reticulum stress, dysregulated immune tolerance, vascular inflammation and endothelial cell dysfunction; however, the prevailing opinion is still that the placenta is the core factor in the pathogenesis of preeclampsia. G protein-coupled receptors, the largest family of membrane proteins in eukaryotes, exhibit diversity in structure and function, mediate cell signaling and are by far the largest drug target family. Among them, Secretin/Adhesion (Class B) G protein-coupled receptors are essential drug targets for human diseases, such as neurological disorders, cancers, endocrine diseases and cardiometabolic diseases. Given the great value of secretin/adhesion (Class B) G protein-coupled receptors in the regulation of cardiovascular system function and drug target development, we summarized the role of these receptors in placental development and preeclampsia and outlined their associated pathophysiological mechanisms, thus providing potential drug targets for preeclampsia treatment.